Evidence points to ‘gaming’ at hospitals subject to National Health Service Cleanliness inspections - Toffolutti, V; McKee, M; Stuckler, D (Project HOPE, 2017)
Inspections are a key way to monitor and ensure quality of care and maintain high standards in the National Health Service (NHS) in England. Yet there is a perception that inspections can be gamed. This can happen, for example, when staff members know that an inspection will soon take place. Using data for 205 NHS hospitals for the period 2011–14, we tested whether patients’ perceptions of cleanliness increased during periods when inspections occurred. Our results show that during the period within two months of an inspection, there was a significant elevation (2.5–11.0 percentage points) in the share of patients who reported “excellent” cleanliness. This association was consistent even after adjustment for secular time trends. The association was concentrated in hospitals that outsourced cleaning services and was not detected in those that used NHS cleaning services.